2023
DOI: 10.1021/acssuschemeng.3c02504
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Glucose Hydrogenation to Sorbitol by Graphene-like Carbon-Encapsulated Ru Catalyst Synthesized by Evaporation-Induced Self-Assembly and Chemical Activation

Abstract: As one of the important value-added chemicals that has wide applications, the catalytic hydrogenation of glucose to sorbitol has been a hot topic in biomass upgrading. In order to support the prosperity of the sorbitol industry, catalysts with superior activity, higher selectivity, longer life, and lower cost are desirable. Herein, tremelliform graphene-like carbon-encapsulated Ru catalysts (Ru/GLC) were synthesized from 4-nitrocatechol by using solvent evaporation-induced self-assembly and KHCO3 chemical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…30,238 Extensive investigations have confirmed that ruthenium carbon catalysts promote hydrogenation of cellulose to sorbitol and show high activity and yields due to hydrogen spillover and electron transfer effects caused by the unique surface contact between ruthenium nanoparticles and carbon-based supports. 61,109,239 Carbon can absorb more hydrogen from Ru spillover and shows excellent adsorption capacity for glucose, thus providing additional catalytic active sites over those of Ru alone. 102 The carbon-based ruthenium materials such as Ru/AC, 103 Ru/CNT 104 and Ru/AG-CNT 106 are efficient catalysts for achieving one-pot conversion of cellulose to sorbitol, possibly due to the abundance of functional groups on the surface and strong Ru–C interactions as compared with other common supports (Fig.…”
Section: Catalyst Development For Sorbitol Productionmentioning
confidence: 99%
“…30,238 Extensive investigations have confirmed that ruthenium carbon catalysts promote hydrogenation of cellulose to sorbitol and show high activity and yields due to hydrogen spillover and electron transfer effects caused by the unique surface contact between ruthenium nanoparticles and carbon-based supports. 61,109,239 Carbon can absorb more hydrogen from Ru spillover and shows excellent adsorption capacity for glucose, thus providing additional catalytic active sites over those of Ru alone. 102 The carbon-based ruthenium materials such as Ru/AC, 103 Ru/CNT 104 and Ru/AG-CNT 106 are efficient catalysts for achieving one-pot conversion of cellulose to sorbitol, possibly due to the abundance of functional groups on the surface and strong Ru–C interactions as compared with other common supports (Fig.…”
Section: Catalyst Development For Sorbitol Productionmentioning
confidence: 99%
“…Therefore, significant efforts have been dedicated to designing and developing catalysts for the green and efficient hydrogenation of glucose to sorbitol, including precious metals ( e.g. , Ru and Pt , ) and nonprecious metals ( e.g. , Ni ,, and Cu).…”
Section: Introductionmentioning
confidence: 99%